Loading and crushing of trapped ballast stones: Loading and deformation of a ballast stone trapped in a railway switch - Hafström, Robin (My University, 2020)
The Swedish railway reported 9000 faults in switches in 2017. One reason for these faults is the trapping of foreign objects in railway switches. However, a number of faults are also due to signaling where a sensor reports a false-positive error. One way to dispense of the problem with erroneous sensors are to remove them. This can only be done if safe operations can be obtained also without sensors. As a first investigation into this, the study will investigate the loading and deformation of ballast stones as well as assess when failure occurs during the switching operation. The study can be divided into two parts: The first part is trying to find the largest stone that could get trapped in the switch when drivers are locking the switch rail. This was done by applying the combined load of two switch motors and a blocking stone in a numerical model and finding where the switch rail had the highest displacement. By testing different boundary conditions it was found that stones smaller than some 42 to 81mm may get trapped under the assumptions in the simulations. The second part of the study concerns the force required to reach failure in a ballast stone. Ballast stones of an approximate diameter of 40mm are investigated. Both numerical simulations and tests were performed. The numerical model used a linear Drucker-Prager material model for the "plasticity" of the stone. The test of the ballast stones was performed using specialised stone crushing equipment. It was concluded that loads in the range of 15 to 60 kN are required to compress the ballast stone 20%. Numerical simulation results and test data did not fit well. This is due to the brittle fracture of the ballast stones not being sufficiently well captured in the numerical simulations.
Keywords: Railway; Switches; contact sensor; Drucker-Prager; Strength of granite; Ballast stone